The Moderating Effect of Technology Utilization on Project Management Function and Project Performance (Malaysian Management Journal, 2013)
This study investigated the moderating effects of technology utilization on the relationship between project management function and project performance. The project management function element is operationalized by nine constructs and the technology utilization element examined in this study focuses on three factors. Data was collected using the questionnaire survey approach. This study employed the stratified random sampling procedure in selecting businesses and organizations, that included the construction industry in the sample. Four hundred and forty eight Aceh construction organizations participated in this study. Partial correlation analysis was utilized for hypotheses testing. In general, the result of the partial correlation analysis showed that technology utilization moderated the relationship between seven of the nine functions of project management and overall project performance. Individually, these three variables of technology utilization did not moderate the relationship between communication management and cost performance. The outcome of this study provided vital information on the relationship between project management function, technology utilization and project performance in the Aceh construction organizations. This study also provided an insight into further understanding of the issue of interface between project management function, technology utilization and project performance.